Detecting changes in distortion product otoacoustic emission maps using statistical parametric mapping and random field theory - Anderson, A. P.; Covington, K. B.; Rieke, C. C.; Fellows, A. M.; Buckey, J. C. (The Journal of the Acoustical Society of America, 2020)
Distortion product otoacoustic emission (DPOAE) maps collect DPOAE emissions over a broad range of frequencies and ratios. One application of DPOAE mapping could be monitoring changes in intracranial pressure (ICP) in space, where non-invasive measures of ICP are an area of interest. Data were collected in two experiments to statistically assess changes in DPOAE maps. A repeatability study where four maps per subject were collected across four weeks to establish “normal” variability in DPOAE data, and a posture study where subjects were measured supine and prone with lower body negative pressure, lower body positive pressure (LBPP), and at atmospheric pressure. DPOAE amplitude maps were analyzed using statistical parametric mapping and random field theory. Postural changes produced regional changes in the maps, specifically in the range of 5–7.5 kHz and between primary tone ratios of 1.13–1.24. These regional changes were most pronounced in the prone LBPP condition, where amplitudes were lower from baseline for the Postural Cohort than the Repeatability Cohort. Statistical parametric mapping provided a sensitive measure of regional DPOAE map changes, which may be useful clinically to monitor ICP noninvasively in individuals or for research to identify differences within in cohorts of people.